PADRÕES DE ESTILO DE UM TRADUTOR LITERÁRIO EM RELAÇÃO À VARIAÇÃO DO VOCABULÁRIO EMPREGADO EM SHOWDOWN E THE WAR OF THE SAINTS - Camargo, Diva Cardoso de (2010)
Having in mind that, even for the disciplines of literary criticism and stylistics, the concept of style is difficult to define, the notion adopted draws on Baker’s (2000:246-7) understanding of style as expressed in a range of linguistic features. In this study, I used a paralell corpus constituted of two target texts into English: Showdown and The War of the Saints, translated by Gregory Rabassa, and their respective source texts belonging to the Brazilian fiction: Tocaia Grande: a face obscura and O Sumiço da Santa, written by Jorge Amado. By contrast with the traditional way of examining whether the author’s style is adequately transposed into the translation, the object of this study is to identify, in the translated text subcorpus, Rabassa’s distinctive style as evidenced in the use of preferred recurring patterns. The task is carried out semi-automatically, through a combination of computerized analysis with WordSmith Tools software package and manual analysis. Considering type/token ratio as an indication of a translator’s individual and recurring vocabulary variation (Baker 2000; Berber Sardinha 2004), the lower 3.52 and 5.56 differences showed by Gregory Rabassa may be seen as a mark of this translator’s individual, distinctive and preferred stylistic patterns in relation to Jorge Amado’s novels analysed.